2021
DOI: 10.1007/s42979-020-00402-w
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality-Based Elementary Level Education for Bengali Character Familiarization

Abstract: Augmented reality is widely used technology in current years in different field of education to enhance the learning process. This study reflects a new way to learn Bengali letters and digits for the early age primary school going children using AR technology. Nowadays, smart phones are very much available in Bangladesh from the rural area to urban area. The proposed method helps to observe interactive 3D view of the characters using mobile camera-based AR application having different options to learn how to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results indicate an increase in the motivation of students, enhancing their overall learning experience, especially for those who are academically lacking. Many studies were conducted to explore the utilization of AR in elementary schools, including the usage of AR to learn natural sciences [82], geometry [92], human anatomy [93], Bengali letters [94], fine arts [95], and science [96]. Another study was conducted in 40 schools in Indonesia to examine the effects of using AR to study science in elementary schools [97].…”
Section: Preschool and Elementary School Educationmentioning
confidence: 99%
“…The results indicate an increase in the motivation of students, enhancing their overall learning experience, especially for those who are academically lacking. Many studies were conducted to explore the utilization of AR in elementary schools, including the usage of AR to learn natural sciences [82], geometry [92], human anatomy [93], Bengali letters [94], fine arts [95], and science [96]. Another study was conducted in 40 schools in Indonesia to examine the effects of using AR to study science in elementary schools [97].…”
Section: Preschool and Elementary School Educationmentioning
confidence: 99%
“…Hossain et al ( 2021 ) modeled augmented reality technologies (ART) that are feasible for early childhood learning. The data suggested that the teachers believe the study represents a positive way of engaging the learning process.…”
Section: Literature Review Of Mobile Learning Resource In Smart Educationmentioning
confidence: 99%